Geoecological assessment of forest landscapes as a basis for the evaluation of ecosystem services - Maksymenko , N. V.; Voronin, V. O.; Burchenko, S. V. (Visnyk of V. N. Karazin Kharkiv National University. Series Еcоlogy, 2023)
Purpose. To study the use of geoecological assessment of forest landscapes as a basis for the assessment of ecosystem services to take into account the natural and anthropogenic conditions of their functioning.Methods. The results of the geoecological assessment were translated into indicators of ecosystem services: provision and regulation.Results. The geoecological assessment of forest landscapes was carried out on a model plot of the Vasyshchivske Forestry of Kharkiv Region, as representative for all forest landscapes of Kharkiv Region - watershed, valley, and beam-thrust. On the basis of the previously conducted geoecological assessment of the forest landscapes of the model area by the means of landscape and ecological planning, the indicator of the amount of ecosystem services to provide for medieval stands by species composition per 1 ha was determined. Thus, on the basis of the Analytical Portal of the state wood accounting system, it was determined that for 2022, the average value of wood by species composition for the Kharkiv region was determined. Thus, the value of the ecosystem service for providing wood is about 604.5 million hryvnias. In terms of unit area (1 ha), the indicator of the ecosystem service will be UAH 13,247/ha. The indicator of the value of ecosystem services for regulation, in particular of the carbon capacity for the model plot, was determined for medieval stands by species composition per 1 ha.Conclusions. The proposed use of geoecological assessment based on the landscape-ecological approach provides an opportunity to take into account landscape conditions, the impact of anthropogenic activity, as well as the results of management decisions in nature management.